2009
DOI: 10.1016/j.visres.2009.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric oxide synthase desensitizes retinal ganglion cells to light by diminishing their excitatory synaptic currents under light adaptation

Abstract: The effect of inhibiting nitric oxide synthase (NOS) on the visual responses of mouse retinal ganglion cells (RGCs) was studied under light adaptation by using patch-clamp recordings. The results demonstrated that NOS inhibitor, L-NAME, reduced the sensitivity of RGCs to light under light adaptation at different ambient light conditions. These observations were seen in all cells that recordings were made from. L-NAME diminished the excitatory synaptic currents (EPSCs), rather than increasing the inhibitory syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…At the retina’s output level, increasing NO was found to decrease Onand Off-responses in RGCs (71). Notably, genetically knocking out nNOS also led to a reduced light sensitivity in RGCs (72), which was also shown by inhibiting nNOS under light-adapted conditions (73). Additionally, NO has been shown to modulate RGC responses via cGMP by altering their cGMP-gated conductances (74, 75).…”
Section: Introductionmentioning
confidence: 92%
“…At the retina’s output level, increasing NO was found to decrease Onand Off-responses in RGCs (71). Notably, genetically knocking out nNOS also led to a reduced light sensitivity in RGCs (72), which was also shown by inhibiting nNOS under light-adapted conditions (73). Additionally, NO has been shown to modulate RGC responses via cGMP by altering their cGMP-gated conductances (74, 75).…”
Section: Introductionmentioning
confidence: 92%
“…This inhibition was mimicked by blocking glycinergic signaling, suggesting the involvement of amacrine cells in this modulation. Conversely, pharmacological inhibition of NO production decreased inhibition onto ganglion cells (Nemargut and Wang 2009). However, ganglion cells in neuronal NOS (nNOS) knockout retinas required more light than wild-type cells to respond optimally, indicating that completely removing nNOS-stimulated NO production also decreases ganglion cell activity (Wang et al 2007).…”
Section: Gabaergic Signaling; Postsynaptic; Modulation the Regulationmentioning
confidence: 99%
“…Previous work from our lab has shown that NO can switch amacrine cell inhibitory synapses into excitatory synapses by moving the equilibrium potential of chloride to more positive values due to the elevation in cytosolic chloride (Hoffpauir et al, 2006 ). Knockouts of neuronal nitric oxide synthase (nNOS) and inhibition of nNOS both reduce the light sensitivity measured in ganglion cells (Wang et al, 2007 ;Nemargut & Wang, 2009 ). These effects of NO, occurring at multiple retinal levels demonstrate the importance of identifying the potential sources of NO in the retina with the long term goal of understanding when and where NO signals are produced.…”
Section: Introductionmentioning
confidence: 99%